Production Safety Supervision Evaluation of Traditional Chinese Medicine: A Fuzzy-ANP Comprehensive Evaluation Method - Wenyi Wang; Jianwang Jiang; Chen Liu; Lei Wang; Xingwang Zhang (Complexity)
Result: (1) Overall, the safety production supervision of TCM in China is relatively sound; however, further efforts are needed to enhance environmental protection in TCM production areas, improve the construction of quality standardization systems, and promote the development of authentic TCM cultivation and breeding; (2) There are significant gaps in the quality control of TCM production enterprises, the innovation and inheritance of classic formulas, and the construction of a traceability system for the circulation of TCM; (3) Listed TCM companies generally exhibit better performance in safety production supervision compared to their nonlisted companies, indicating that a strict and comprehensive regulatory system helps to improve the level of safety production supervision for TCM.